Study on cutting force performance and cutting mechanism of Carbon Fiber Reinforced Polymer (CFRP) composites - Zeyu DUAN; Guangjun LIU; Xiangdong FAN; Tao CHEN (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2021)
CFRP materials are widely used in special environments, and it has excellent mechanical properties. However, CFRP processing is very difficult, especially in the process of using traditional cutting methods, due to its heterogeneity and anisotropy. In this work, based on the failure mechanism of CFRP materials, we studied the cutting mechanism of the cutters in milling processing, modeled and analyzed the milling cutters and processing materials, and conducted orthogonal milling experiments of CFRP composite materials. Based on the experimental data, the influence of different machining parameters on the cutting force was studied, and the relationship between the influence of different cutting methods on the cutting stress and cutting heat on the life of the milling tool was obtained. According to the angle between the fiber orientation and the cutting edge of the cutting edge, the cutting behavior of single fiber and CFRP unidirectional laminate is classified. The failure modes of CFRP materials under different processing behaviors are predicted and analyzed, and the theoretical model is simulated by the finite element method. The CFRP milling process and failure process are theoretically analyzed, and the milling failure process and failure forms are summarized. Through the finite element simulation of the failure process and the section observation under the scanning electron microscope, the cutting mechanism of the CFRP material is analyzed, which provides a reference for optimizing the milling parameters and optimizing the mechanism.